Analisis Faktor yang Berhubungan dengan Kehadiran Ibu pada Kelas Ibu Hamil - Hajinah, Ferriyal Sepriza Fauzan; Kurniati, Mala; Yanti, Dhiny Easter; Anita, Anita; Muhani, Nova (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT One of the main agendas of the SDGs is to reduce maternal and under-five mortality rates. Quality and regular antenatal examinations during pregnancy will determine the health status of the pregnant mother and the baby born. Pregnant women's classes are included in the community health center program. This study aims to analyze factors related to the presence of mothers in pregnant women's classes at the Negara Batin Community Health Center, Tanggamus Regency in 2023. Therefore, this research focuses on analyzing factors related to the presence of mothers in the pregnant women's class at the Negara Batin Public Health Center, Tanggamus Regency in 2023. The research method used was quantitative with a cross sectional design. The sample taken was 91 respondents and were pregnant women using the total population technique. Data analysis uses univariate, bivariate analysis, namely Chi-Square and multivariate, namely Logistic Regression. The results of the study found that those related to maternal attendance in the pregnant mother class were maternal motivation (p: 0.001), husband's support (p: 0.037, OR 2.8), support from health workers (p: 0.000, OR 8), and affordability of health facilities. (p: 0.000, OR 10.3). The most dominant factor related is maternal motivation with an Exp (B) value of 32.258, which means that pregnant mothers with low motivation are 32 times more motivated than good mothers. It is hoped that these results can become a reference for community health centers to improve the quality of health services so that the attendance of mothers in pregnant women's classes increases. Keywords: Class for Pregnant Women, Motivation, Mothers.  ABSTRAK Salah satu agenda utama SDGs adalah menurunkan angka kematian ibu dan kematian Balita. Pemeriksaan antenatal yang berkualitas dan teratur selama kehamilan akan menentukan status kesehatan ibu hamil dan bayi yang dilahirkan. kelas ibu hamil termasuk dalam program puskesmas. Penelitian ini bertujuan unutukanalisis faktor yang berhubungan dengan kehadiran ibu pada kelas ibu hamil di Puskesmas Negara Batin Kabupaten Tanggamus Tahun 2023 . Oleh karena itu, penelitian ini memfokuskan pada analisis faktor yang berhubungan dengan kehadiran ibu pada kelas ibu hamil di Puskesmas Negara Batin Kabupaten Tanggamus tahun 2023. Metode penelitian yang digunakan kuantitatif dengan rancangan Cross Sectional. Sampel yang diambil sebanyak 91 responden dan merupakan ibu hamil dengan teknik total populasi. Analisis data menggunakan analisis univariat, bivariat yaitu Chi-Square dan multivariat yaitu Regresi Logistik. Hasil penelitian didapatkan yang berhubungan dengan kehadiran ibu pada kelas ibu hamil adalah motivasi ibu (p:0,001), dukungan suami (p:0,037, OR 2,8), dukungan petugas kesehatan (p:0,000, OR 8), dan keterjangkauan fasilitas kesehatan (p:0,000, OR 10,3). faktor yang paling dominan berhubungan adalah motivasi ibu dengan nilai Exp (B) sebesar 32,258 yang artinya ibu hamil dengan motivasi rendah 32 kali lebih daripada motivasi ibu baik. Hasil ini diharapkan dapat menjadi acuan bagi puskesmas untuk meningkatkan mutu pelayanan kesehatan agar kehadiran ibu dikelas ibu hamil meningkat. Kata Kunci: Kelas Ibu Hamil, Motivasi, Ibu.